KONSEP MAHABBAH RABIAH AL-ADAWIYAH DALAM PENDIDIKAN ISLAM PERSPEKTIF MARGARET SMITH - RAJA LOTTUNG SIREGAR; Akmalia Safitri (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2025)
In human life the concept of mahabbah is very important, especially in the study of Islamic education. Because in starting the education, students should love their teachers as well as teachers must love their students. Thus, the lesson will be easy for students to understand. The purpose of this study is to find out the concept of mahabbah according to Rabi'ah Al-Adawiyah, To find out the concept of mahabbah Rabi'ah Al-Adawiyah in Islamic Education Perspective Margaret Smith. This research method is library research, namely a study, to obtain a number of necessary data purely only utilizing sources available in the library. The results of this study are that the concept of mahabbah according to Rabi'ah Al-Adawiyah is: first, love only for Allah and turning away from others. Sufis must close their eyes to the world and its contents and attractions. Second, love only for Allah and selflessly. Not expecting a reward in the form of rewards or punishments. The concept of mahabbah rabi'ah al adawiyah in Islamic education from Margaret Smith's perspective is: Zuhud, Purifying oneself (takhalli), Filling oneself with good morals (tahalli), Habituation (tajalli).